Phosphate as a limiting factor for the improvement of single cell oil production from Yarrowia lipolytica MUCL 30108 grown on pre-treated distillery spent wash. (October 2020) - Hoarau, Julien; Petit, Thomas; Grondin, Isabelle; Marty, Alain; Caro, Yanis
Graphical abstract: Highlights: Cellulolytic enzymes and fungal extracts of A. niger upgrade the digestibility of DSW. Addition of 7 g/L potassium phosphate in DSW increased yeast biomass by 70 %. Microbial lipids mainly composed of fatty acids (saponifiable lipids) are generated. Fatty acid composition is similar to microbial and plant oils used in biodiesel production. Abstract: One of the major environmental problems is the industrial waste called vinasse, also known as Distillery Spent Wash (DSW) produced in large amount by ethanol distilleries. In this study, we aimed at to improve the production of single cell oil (SCO) using the oleaginous yeast Yarrowia lipolytica MUCL30108 on DSW and to determine the main factor influencing biomass production. Growth of Y. lipolytica was assessed on DSW with modifications of the effluent for biomass production. Chemical acid hydrolysis, enzymatic hydrolysis with cellulases and hemicellulases, or by mobilizing the hydrolytic tools of Aspergillus niger MUCL19001 were used as pretreatment to improve sugar release in the effluent and to improve yeast biomass production. Subsequently, the impact of pH adjustment and of vitamins, glucose and minerals supplementation was investigated to understand the specific nutritional and physiological limitations of the yeast biomass production. The pretreatment of DSW with A. niger cellular extracts provided the highest release of reducing sugars (up to 5.65 g/L), principally composed of glucose and a 30 % increase in yeast biomass production as compared to crude DSW. Additionally, addition of potassium phosphate resulted in a significant improvement of the yeast biomass production, reaching up to 70 % increase as compared to crude DSW without affecting the lipid content of the yeast biomass. The microbial lipids produced were mainly composed of fatty acids suitable for biodiesel valorisation. Globally, our findings suggested that phosphate, but not the carbon source, was the major limiting factor for growth of the yeast in raw DSW.